2015
DOI: 10.1007/s10812-015-0068-1
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Optical Properties of CdI2 Nanostructures

Abstract: Nano-sized structures (nanopores, nanoclusters, nanowires) that formed on van-der-Waals surfaces of CdI 2 during their curing in air under near-equilibrium thermodynamic conditions were found using atomic-force microscopy. A mechanism of nanocluster formation was proposed. They nucleated and grew in nano-sized pores. Aggregation of the nanoclusters gave rise to the formation of nanowires. Photoluminescence and Raman spectroscopy showed that the nanoclusters contained cadmium hydroxide [Cd(OH) 2 )] and oxide (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The transformation of CdI 2 photoluminescence spectra over time, as supported by atomic force microscopy results, may be connected with the creation of nanostructures on the crystal surface [4,[22][23][24] and with the modification of the crystal structure: the annihilation of moving defects and the appearance of PbI 2 nanophases.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…The transformation of CdI 2 photoluminescence spectra over time, as supported by atomic force microscopy results, may be connected with the creation of nanostructures on the crystal surface [4,[22][23][24] and with the modification of the crystal structure: the annihilation of moving defects and the appearance of PbI 2 nanophases.…”
Section: Resultsmentioning
confidence: 78%
“…It was shown [22][23][24] that nanostructures are formed on the surface of CdI 2 crystals in the process of their aging in air. The formation mechanisms of nanostructures involve several stages: inception, growth and interaction between individual structures.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Cadmium iodide (CdI 2 ) crystals are long known for their descent scintillating properties which have been extensively studied by spectroscopic techniques. [5][6][7][8][9][10][11][12] Comparing it with other scintillators and phosphors [13][14][15][16][17][18][19][20][21] it shows comparable detector characteristics in some parameters, and therefore it is still of interest, especially when considering its improvement by doping. [22][23][24] Among existing and potential application areas of CdI 2 , one can mention detectors, photolithography, and optical recording.…”
Section: Introductionmentioning
confidence: 99%
“…In works [6,7], we studied cadmium iodide crystals grown from a melt. With the help of AFM methods, we found that if CdI 2 crystals are held in the air environment under thermodynamically equilibrium conditions, nanostructures (nanopores, nanoclusters, and nanowires) are formed on their surface.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, there are practically no works dealing with the surface topology and the formation of nanostructures in non-stoichiometric cadmium iodide crystals grown from a melt. Such studies are important because cadmium atoms are a building material for the nanostructure formation [6,7]. Therefore, the aim of this work was to study the morphology and phase composition of nanostructures emerging on the surface and in the bulk of non-stoichiometric CdI 2 crystals, as well as the influence of those nanostructures on the material optical properties.…”
Section: Introductionmentioning
confidence: 99%